Empowering sustainable transitions: The Living Lab for People in Colombia - Vanegas Cubillos, Martha Cristina; Rodriguez, Luz Angela (2023)
In the realm of innovation and sustainability, a groundbreaking approach is taking root: the Living Lab for People (LL4P) in Caquetá, Colombia. This visionary concept introduces a physically embedded innovation cluster within existing organizational structures, aiming to foster environmentally and economically sustainable alternatives, especially in vulnerable communities.